Diary of Nicholas Garry, Deputy-Governor of the Hudson's Bay Company from 1822-1835 [electronic resource] : a detailed narrative of his travels in the Northwest Territories of British North America in 1821 - Garry, Nicholas, 1781?-1856; Royal Society of Canada. ([S.l. : s.n., 1900)
From Transactions of the Royal Society of Canada, section II, 1900. "With a portrait of Mr. Garry and other illustrations." "Communicated to the Society through Sir John Bourinot, and read May 29, 1900." Electronic reproduction. Mode of access: Internet. 44